2009
DOI: 10.1159/000222775
|View full text |Cite
|
Sign up to set email alerts
|

Refractory Epilepsy: A Clinically Oriented Review

Abstract: About one third of patients with newly diagnosed epilepsy do not achieve seizure control despite medical therapy and should be assessed in detail to confirm the diagnosis, to determine the epilepsy syndrome and to plan treatment strategy. Refractory epilepsy is established when there is inadequate seizure control despite using potentially effective antiepileptic drugs (AEDs) at tolerable levels for 1–2 years, and excluding nonepileptic events and poor compliance. An overview of patient management in everyday c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0
9

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(66 citation statements)
references
References 97 publications
1
56
0
9
Order By: Relevance
“…But, even these have limited utility and search is on for newer more effective AEDs. 21 Pharmacoresistance is explained intrinsic severity hypothesis, the target hypothesis and the transporter hypothesis. 22 Drug related factors like tolerence have also been involved in development of pharmacoresistance.…”
Section: Discussionmentioning
confidence: 99%
“…But, even these have limited utility and search is on for newer more effective AEDs. 21 Pharmacoresistance is explained intrinsic severity hypothesis, the target hypothesis and the transporter hypothesis. 22 Drug related factors like tolerence have also been involved in development of pharmacoresistance.…”
Section: Discussionmentioning
confidence: 99%
“…A investigação e determinação da provável ZE dentro deste plano pode ser realizada através de algumas abordagens, incluindo análise de semiologia, história clínica, imagens de ressonância magnética, imagens funcionais (PET e SPECT), e eletroencefalografia [14]. Todavia, mesmo com o uso de todas essas técnicas, a determinação da ZE nem sempre é possível, e nestes casos, o paciente é impedido de realizar a cirurgia.…”
Section: Epilepsia Refratáriaunclassified
“…Considerando m=1 e o vetor x1={u(1)}, seu padrão é repetido três vezes em {u(7)},{ u(14)}, {u(31)}. Ao considerar o vetor x2={u(1),u(2)} para m+1=2, nota-se que somente dois dos padrões anteriores ainda se repetem, em {u (14),u(15)} e {u (31),u(32)}. O xii mesmo pode ser observado considerando o vetor x2={u(1),u(2)} para o caso m=2.…”
unclassified
“…According to Beleza (2009), refractory epilepsy is established when there is inadequate seizure control despite using potentially effective AEDs at tolerable levels for 1 to 2 years. Refractory epilepsy patients show increased risk of psychiatric, psychosocial, and medical morbidities.…”
Section: Refractory (Intractable) Epilepsymentioning
confidence: 99%
“…Various studies have suggested that onset of early intractable seizures may be a significant risk factor for impairment of intellectual functioning and adaptive abilities (Saneto and Wyllie, 2000). Resective surgery, based on the removal of the entire epileptogenic area without causing permanent neurological deficit, is one of the treatment forms for refractory epilepsy (Beleza, 2009). In surgical series, focal cortical malformations and low-grade tumors were the most common in infants with intractable epilepsy.…”
Section: Refractory (Intractable) Epilepsymentioning
confidence: 99%